Galvanising SMK baging with English - Wan Jumani, Fauzi (Pusat Bahasa Moden dan Sains Kemanusiaan, 2010)
5 - 6 March 2010. The Penilaian Menengah Rendah (PMR) English Writing Workshop was aimed at galvanising 70 Form Three students of Sekolah Menengah Baging to have a ball with English while at the same time learn how to tackle writing through new strategies.